Perception and smoking status among primary healthcare center staffs as predictors of support for a 100% smoke-free policy in a mixed rural-urban area - Harisaputra, Rosalia Kurniawati; Indriani, Citra; Prabandari, Yayi Suryo (Berita Kedokteran Masyarakat, 2026)
Purpose: Focusing on primary healthcare personnel at the district level in Indonesia and integrating behavioral theory and contextual tobacco-control factors, this study aims to analyze health staff attitudes toward implementing a 100% smoke-free policy in primary healthcare centers (PHCs). Methods: This study utilized secondary data from Quit Tobacco Indonesia. The survey, conducted between 2011 and 2012, focused on staff employed at PHCs in Bantul District, Special Region of Yogyakarta. The study employed a cross-sectional design with 313 participants. The dependent variable in this study was attitude towards a 100% smoke-free policy in PHCs. The independent variables were beliefs regarding the effects of environmental tobacco smoke (ETS) and perceptions of ETS. Covariate variables included staff position, gender, educational level, training on the smoking problem, smoking status, knowledge level about the impacts of ETS, medical staff as role models, age, and length of working. Analysis was conducted using descriptive (proportion) and bivariable (chi-square) approaches, as well as multivariable (multiple logistic regression). Results: Individuals who perceived ETS exposure negatively (OR 16.6; 95%CI: 6.59-42.1), and those with a non-smoking status (OR 20.3; 95%CI: 7.43-55.3) or former smoking status (OR 6.7; 95%CI: 1.73-26.0), were more likely to demonstrate a favorable attitude toward a 100% smoke-free policy in PHCs. Conclusion: Stakeholders such as the district health office and PHC heads can strengthen smoking cessation efforts through education and financial strategies to help current smokers transition to former smokers.